Librarians'challenges in teaching information literacy / Haslinda Husaini - Husaini, Haslinda (Faculty of Information Management, 2010)
Mastering information literacy skill is essential in ensuring effective research, learning and communication, decision-makings and problem-solvings for university students. Despite living in the age of technological advancement, teaching information literacy skills to students continues to be a challenge for both librarians and academicians. It has become a fundamental responsibility for librarians.